The Wings Of The Morning - Tryon, Thomas (New York Fawcett Crest, 1992)
Pequot Landing, Connecticut, is not the place--nor is this the time--for love. Yet Aurora Talcott and Sinjin Grimes are struck with it as by a thunderbolt--only to be violently separated by their feuding elders and catapulted to opposite ends of the earth: she to aristocratic England, and he to the trading hongs of Macao and the pirate seas of China. And left behind at home, growing stronger from her own desperate strugle, is Georgiana, the hired girl whose secret story entwines the fates of them all....
Keywords: Connecticut